1989
DOI: 10.3109/13813458909075070
|View full text |Cite
|
Sign up to set email alerts
|

The response of rat adrenal medulla to oxytocin

Abstract: Effects of oxytocin (OT) on the adrenal chromaffin tissue of male rats were examined by coupled morphometric and biochemical techniques. Synthetic OT was administered in doses of 0.14 and 0.25 IU/100 g/d during 7 or 10 consecutive days and the effects were followed 1, 24, 72 and 168 hours after the last injection. The function and structure of chromaffin cells were affected by the higher dose of OT only. They caused divergent responses on their amine contents. Adrenaline, noradrenaline and dopamine contents we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

1990
1990
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…The finding that OT stimulates the mitotic activity of adrenomedullary chromaffin cells of intact male rats fits well with our previously reported data on its effect on the number of chromaffin cells (Plecas et al 1989). In the present study the effect of OT is evident on the 3rd day of the treatment.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The finding that OT stimulates the mitotic activity of adrenomedullary chromaffin cells of intact male rats fits well with our previously reported data on its effect on the number of chromaffin cells (Plecas et al 1989). In the present study the effect of OT is evident on the 3rd day of the treatment.…”
Section: Discussionsupporting
confidence: 93%
“…The influence of this neuropeptide on catecholamine secretion has already been shown (Gibbs 1986;Nussey et al 1987). In a previous study {Plecas, Ugresic, Hristic, Popovic and Jovovic 1989) we revealed, by means of stereology, that in male rats OT enhanced the total number of adrenomedullary chromaffin cells, which indicated a mitotic action. No data on the mitogenic effect of OT on the chromaffin tissue are available, and because of that we examined the mitogenic potency of OT using a metaphase arrest technique.…”
Section: Introductionmentioning
confidence: 58%
“…Otr delineates a subset of nNos+ SPNs projecting to the AM Next, we sought SPNs targeting the AM. Based upon literature suggesting an association between the neural hormone oxytocin (OT) and AM functions [28][29][30] , along with the documented expression of Otr mRNA in the IML of the SC 31 , we identified Otr+ SPNs as specific projectors to the AM. First, utilizing the RNAscope single-molecule in situ hybridization method, we found that the majority of Otr+ cells were nNos+ in the IML of the thoracic SC (Extended Data Fig.…”
Section: Cartpt+ Spns Selectively Project To the Cg/smgmentioning
confidence: 99%
“…OT exerts effects also on the adrenal medulla. It was shown that chronic OT treatment leads to increased epinephrine and norepinephrine the rat adrenal medulla [62]. Moreover, it exerts bidirectional effects on the adrenal cortex where increased corticosterone levels were associated with acute OT administration.…”
Section: Effects Of Endogenous and Exogenous Ot On The Social Behaviourmentioning
confidence: 99%